Features of the phenological phases of introduced strawberry cultivars in the conditions of the Orel region - M. I. Zubkova; S. D. Knyazev; I. E. Evtikhova (Овощи России, 2021)
Relevance. The study of the timing and duration of individual phases of the development of strawberry cultivars of different ecological and geographical origin in these climatic conditions is of great practical importance. The purpose of the study was the determination of the timing of the main phenophases of introduced strawberry cultivars in the Orel region, the compliance of the phenorhythms of the studied cultivars with climatic conditions, as well as the ranking of the cultivars by the terms of flowering and maturation.Methods and materials. The article presents the results of phenological observations for the period 2016-2019. 34 strawberry cultivars of domestic and foreign selection were studied. The research was carried out at the VNIISPK site of primary variety study.Results. Based on long - term observations, on the time of entry into the flowering and fruiting phase, the cultivars were ranked into early, medium and late-maturing. The influence of effective temperatures on the onset of phenophases was analyzed. The sum of effective temperatures necessary for the beginning of flowering of strawberry cultivars of different maturation periods in the conditions of the Orel region was determined. For the onset of strawberry flowering, it takes from126.68 to 260.37°effective temperatures. Early cultivars need the sum of effective temperatures of 126.68-197.55°, cultivars of middle maturation need 146.31-225.44°, late cultivars - 159.93-260.37 depending on the year of study. Fruiting occurs at the sum of effective temperatures in early cultivars from 351.73°C to 465.43°C, in middle-maturing cultivars from 390.96 to 535.44°C, in late-maturing cultivars from 450°C to 649°C.